Sammenligning av metoder for eluering av IgG-antistoff bundet til erytrocytter - Elin Hallheim Reiersøl; Thomas E. Hundhausen (Bioingeniøren)
Background: IgG antibodies bound to erythrocytes may be involved in various disease processes. Identification of these antibodies and antigen typing of patients with a positive direct antiglobulin (DAT) test is relevant both for transfusion therapy and follow-up of patients during pregnancy. We have compared elution efficiency and concordance of results for various CE (Communauté Européenne) and IVD (In vitro Diagnostic) labelled methods and heat elution.